FINANCIAL MANAGEMENT STRATEGY IN ONLINE SHOP IN SOUTH SULAWESI - Nurmawaddah; Siti Aisyah; Firman Syah (International Journal of Economic Research and Financial Accounting, 2024)
This study is a qualitative research aimed at understanding the financial management strategies applied by online shops in South Sulawesi. The type and sources of data used are primary data and secondary data. The data collection methods involve observation, interviews, and documentation with a total of five research subjects. The results indicate that all research informants, as online shop owners, still apply relatively simple financial management practices, but there has been improvement as they now detail every transaction conducted. Although they are fairly good at reporting finances, there is still room for improvement. Therefore, it is recommended that online shop owners deepen their understanding of financial management more comprehensively.